2010
DOI: 10.1258/ijsa.2008.008459
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the introduction of rapid HIV testing in the Voluntary Counselling and Testing sites network of Catalonia, Spain

Abstract: Rapid HIV antibody tests, which provide results within 15-60 minutes, can help reduce the number of unrecognized infections by improving access to testing facilities and increase the number of people tested who know their results. After an acceptability study, rapid HIV testing was first implemented in Catalonia in 2007 within the community-based Voluntary Counselling and Testing sites network. One year after implementation, an increase of 102.9% has been observed in the number of tests performed, ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 7 publications
3
21
0
2
Order By: Relevance
“…The prevalence of infection (1% overall and 3.8% in MSM) is similar to that found in other programmes not aimed at high-risk groups [35,36] and slightly higher than that found in the only previous paper published on in-pharmacy testing, in another Spanish region (0.85%) [17] It is three times higher than that found in a study of the use of pharmacies as a recruitment site [16].…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of infection (1% overall and 3.8% in MSM) is similar to that found in other programmes not aimed at high-risk groups [35,36] and slightly higher than that found in the only previous paper published on in-pharmacy testing, in another Spanish region (0.85%) [17] It is three times higher than that found in a study of the use of pharmacies as a recruitment site [16].…”
Section: Discussionsupporting
confidence: 81%
“…This review identified a limited number of testing initiatives that demonstrated an increase in HIV testing, as a conseqence of a lack of reporting of baseline data or control data. Only two comparative studies presented data documenting changes to the number tested over time . One study, describing a community‐based voluntary counselling and testing service for MSM, showed a scale‐up from 951 tests carried out in 2009 to more than 4049 in 2012; reactivity over this period remained stable (3.9% in 2007; 3.4% in 2012) .…”
Section: Resultsmentioning
confidence: 99%
“…Despite an extensive number of interventions that seek to increase knowledge of HIV serostatus among MSM, global test uptake remains low (Arreola, Hebert, Makofane, Beck, & Ayala, 2012). Barriers to accessing HIV services at traditional health care settings are numerous (Krause, Subklew-Sehume, Kenyon, & Colebunders, 2013; Myers, El-Sadr, Zerbe, & Branson, 2013; Song et al, 2011; Tucker, Bien, & Peeling, 2013) and have led to a significant increase in alternative programmes that offer rapid, point-of-care HIV testing in community-based settings (Bowles et al, 2008; Fernandez-Lopez et al, 2010). Globally, rapid tests for HIV have been used for almost a decade, but the need to attend a health facility has severely impeded test uptake among key populations (Tucker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%